2017
DOI: 10.1111/pcn.12546
|View full text |Cite
|
Sign up to set email alerts
|

Increased beta power in the bereaved families of the Sewol ferry disaster: A paradoxical compensatory phenomenon? A two‐channel electroencephalography study

Abstract: This study suggests that increased beta power, reflecting the psychopathology in the bereaved families of the Sewol ferry disaster, may be a compensatory mechanism that follows complex trauma. Frontal beta power could be a potential marker indicating the severity of sleep disturbances. Our results suggest that sleep disturbance is an important symptom in family members of the Sewol ferry disaster's victims, which may be screened by EEG beta power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 60 publications
0
10
0
1
Order By: Relevance
“…In PTSD, left FAA is dominant [6,32]. The BFM with suicidal ideation in our study showed a right-sided dominance in FAA, which indicated disorganized negative emotion processing related to bereavement with suicidal ideation [35]. BFM have neurophysiological characteristics that are opposite to those of patients with PTSD.…”
Section: Discussionmentioning
confidence: 84%
“…In PTSD, left FAA is dominant [6,32]. The BFM with suicidal ideation in our study showed a right-sided dominance in FAA, which indicated disorganized negative emotion processing related to bereavement with suicidal ideation [35]. BFM have neurophysiological characteristics that are opposite to those of patients with PTSD.…”
Section: Discussionmentioning
confidence: 84%
“…A two-channel EEG and HRV detecting wearable device (model: Amp GS5001; SOSO H&C, Kyungpook University, Daegu, Korea) was previously used for orthopedic spinal surgery and a psychiatric study [11,12]. This wearable device has attachment sites corresponding to Fp1 and Fp2 that reflect the brain's frontal lobe cortical activity.…”
Section: Methodsmentioning
confidence: 99%
“…One study evaluating functional connectivity of resting-state EEG in PTSD patients reported results of reduced connection strength and communication efficiency in beta and gamma frequency bands [ 23 ], and another study reported disrupted global indices (strength, clustering coefficient, path length, and efficiency) in delta, theta, low beta frequency bands of resting-state EEG in PTSD subjects [ 24 ]. A more recent study of bereaved families following a national trauma has reported increased frontal beta powers, suggesting possible compensatory mechanisms following a complex trauma [ 25 ].…”
Section: Introductionmentioning
confidence: 99%